The daughter of Auschwitz my story of resilience, survival and hope - Friedman, Tova 1938; Brabant, Malcolm; Kingsley, Ben, 1943- (Toronto, Ontario Hanover Square Press, 2022)
Holocaust survivor Friedman recalls her experiences in Auschwitz-Birkenau as a young child in this heartrending memoir. Born in Tomaszow Mazowiecki, Poland, in 1938, Friedman's first memories were of life in the Jewish ghetto. Suffering starvation, disease, and constant violence, she and her parents managed to survive several deportations and mass killings by the Gestapo. In autumn 1943, however, the family was deported to a slave labor camp in central Poland, and then taken in July 1944 to Auschwitz, where Friedman and her mother were separated from her father. "It's estimated that more than 230,000 children entered the Auschwitz complex," she notes. "Almost all of them were murdered in Birkenau within hours of dismounting from the cattle cars.... So why wasn't I?" That question lingers over her harrowing memories of the camp, including the time she and her block mates huddled for hours in the concrete anteroom for one of the gas chambers before being sent back to their barrack. After the war, Tova was reunited with her father, emigrated with her parents to America, married, and began sharing "the lessons of the Holocaust" in Israel and the U.S. Enriched by Friedman's earnest reckonings with her trauma and hard-won sense of optimism, this is a poignant testament to survival and faith.
111182
Keywords: Friedman, Tova -- 1938; 1939-1945; Holocaust, Jewish (1939-1945) -- Personal narratives; Holocaust survivors -- Biography; Nazi concentration camps -- Germany; World War, 1939-1945 -- Concentration camps -- Liberation; Internment camps; Liberty; Autobiographies; Biographies